Comparison of plasma ALZpath p-Tau217 with Lilly p-Tau217 and p-Tau181 in a neuropathological cohort - Divya Bali; Gemma Salvadó; Thomas G. Beach; Geidy E. Serrano; Alireza Atri; Eric M. Reiman; Andreas Jeromin; Oskar Hansson; Shorena Janelidze (Acta Neuropathologica Communications)
Abstract There is an urgent need for accurate and validated methods to measure plasma phosphorylated tau (p-Tau) biomarkers in Alzheimer’s disease (AD). In this study, we compared the performance of new commercially available plasma p-Tau217 assay developed by ALZpath to other established p-Tau assays in an autopsy-confirmed sample. We included 72 participants from the Arizona Study of Aging and Neurodegenerative Disorders cohort, with antemortem plasma assessments and postmortem neuropathological examination. Plasma p-Tau217 was measured using the single molecule arrays (SIMOA)-based ALZpath immunoassay and plasma p-Tau217 and p-Tau181 were analyzed with mesoscale discovery (MSD)-based immunoassays developed by Lilly Research Laboratories. Plasma biomarkers were compared with densities of post-mortem-assessed amyloid plaques and neurofibrillary changes. Levels of p-Tau217ALZpath, p-Tau217Lilly and p-Tau181Lilly were significantly associated with plaque (partial Spearman ρ = 0.58, ρ = 0.78, ρ = 0.65; p < 0.001) and neurofibrillary (ρ = 0.26, ρ = 0.51, ρ = 0.37; p < 0.05) density scores, adjusting for age, sex, and time of interval between blood sampling and death. All three biomarkers were also significantly associated with plaque density scores (p-Tau217ALZpath, ρ = 0.53; p-Tau217Lilly, ρ = 0.73; p-Tau181Lilly, ρ = 0.59; p < 0.001), when additionally adjusting for neurofibrillary density scores. However, only p-Tau217Lilly was significantly associated with neurofibrillary density scores (ρ = 0.32, p = 0.022), when adjusting for plaque density scores. The correlations of p-Tau217ALZpath and p-Tau181Lilly with plaque density scores were comparable, whereas p-Tau217Lilly exhibited significantly higher correlations with plaques (pdiff≤0.015) and neurofibrillary changes (pdiff≤0.004) than p-Tau217ALZpath. While p-Tau217ALZpath and p-Tau181Lilly predicted the presence of Alzheimer’s disease neuropathological change (ADNC), Braak staging (Braak 0-IV vs. Braak V-VI) and CERAD neuritic plaque classification (low/sparse vs. moderate/frequent) with similar accuracies (area under the curve [AUC]range, 0.74–0.79), p-Tau217Lilly AUCs were significantly higher (AUCrange,0.82–0.89, pdiff≤0.024) than the AUCs of p-Tau217ALZpath. In conclusion, p-Tau217ALZpath exhibited similar performance as p-Tau181Lilly but its correlations with core measures of AD pathology were significantly lower in comparison with p-Tau217Lilly. Future studies are warranted to replicate these findings in larger independent cohorts.